A modified CPS-PWM for capacitor voltage reduction of MMC based variable speed drive - Safia Babikir Bashir; Hasan Abdel Rahim A. Zidan; Zulfiqar Ali Memon (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
In recent years, modular multilevel converters (MMC) have become one of the most popular multilevel converter topologies. Despite its growing popularity, MMC is still less widespread in variable speed drives (VSDs) applications. The reason for this is that the voltage ripple of the MMC submodules (SM) increases during the low-speed constant torque operation. In this paper, carrier phase shift-pulse width modulation (CPS-PWM) is modified to reduce the average voltage of SM and thus accommodate more ripples without exceeding the maximum SM voltage. The proposed method does not involve the injection of circulating current components, thereby resulting in less power loss. In addition to that, the necessity for increasing the SM capacitor rating during low-speed operation is not required. Extensive simulation has been conducted under various speed commands to validate the effectiveness of this method.